Avaliação do acúmulo de debris e áreas não instrumentadas do canal após o preparo com os sistemas Pro Taper Next e TF Adaptive - Lopes, Rosa Maria Vianna (2016)
The present study assessed the amount of hard-tissue debris accumulation and the percentage of non-instrumented area of root canals prepared with ProTaper Next (PTN) and TF Adaptive (TFA) systems using micro-computed tomographic imaging (micro-CT). Twenty isthmus-containing mesial roots of mandibular molars were anatomically matched based on similar morphological dimensions using micro-CT evaluation (resolution of 14.16 μm) and assigned to 2 experimental groups (n = 10) according to the system used for root canal preparation: PTN and TFA. Then, specimens were scanned again and the matched images of the mesial canals, before and after preparation, were examined from the furcation level to the apex to evaluate the amount of hard-tissue debris and to quantify the non-instrumented surface canal areas. An independent samples t-test and a Mann-Whitney test were respectively used to compare these variables between the groups with a significance level set at 5%. Root canals prepared with either PTN or TFA systems were found to present similar hard-tissue debris accumulation and non-instrumented surface areas (P =0.39 and P = 0.52, respectively). Both systems were not able to yield root canals completely free from packed hard-tissue debris; they produced a suboptimal mechanical preparation of the mesial canals of mandibular molars.